MODEL INCREASING SATISFIED BASED ON THE CUSTOMER VALUE: STUDY ON CUSTOMER AT LIBRARY STATE POLYTHECNIC OF JAKARTA - Sudarno Sudarno; Amirudin Amirudin (Ekonomi & Bisnis, 2015)
Abstract More than 32 years library State Polythecnic of Jakarta served civitas academica waiting oriented (passive). Statistics data showed that customer of library State Polythecnic of Jakarta last five years not significant. (Source: Anual Book Report 2014). Because of that, its time to library management applied new paradigmn service based on ‘the customer value.’ It means that applied with adagium customer will increase followed by increasingly accredited higher education institution. (Source: American Librarian Association, 2013) Claimed of National Institution Accreditation is very important for State Polytechnic Of Jakarta in the future (2029, PNJ go international) will be followed by Claimed of International Institution Accreditation. Because of that, the role from customer is really important to develop the State Polytechnic Of Jakarta. If customer feels satisfied for pursuit State Polytechnic Of Jakarta’s Library, the impact is following another outsearches. The aim of research (1) are knowing and measuring (1) the costumer value, and (2) applied the costumer value, in order to customer volume from years by years tend to significantly increase. (2) Having a model to develop library and serve costumer base on the customer value in order to applied to another units in State Polytechnic Of Jakarta. Metode of research using descriptive analysis by spreading quesioner from some population and taken sample after that change into table, tested and analysed and taken the purpose. The definition of the newest edition from library glossarium is the newest print between 1-5 period, meanwhile book of print between 5-10 is called the old edition. Altough the book was a old version the frequence always borrowed by the customers , so the book will still considered as the new one. However the book that published more than 10 years was a rare book which is the frequence often borrowed by the customers. Lets see the collection of the book in library PNJ based on the tender of purchase in 2013. Since a part of 807 book title, it’ll be 53 book title published between 1-5 years period. Those books the writer explained on Chapter IV. PNJ library should be use ‘book showcase’, social media and website for informing the newest book availability and active controlled and in secquencing. First, we recommended to library managment on websites for avaliability ‘book delivery order’ in order to student for not spending time. Second, to motivate students visiting library of PNJ inform via student’s email that avaliability book newest edition ready to lend. Keywords : pemustaka, The Customer Value, The Customer Satisfaction, book delivery order, book showcase